INFORMATION TECHNOLOGY IN THE WORK OF TEACHERS IN PRE- SCHOOL EDUCATION - BUŁKA, Beata; FIEBICH, Łukasz (Trends in education, 2010)
The dynamic progress of information technologies simplifies the teachers work, varies the education process and causes that learning is going to be an enjoyable "adventure". To make this real every teacher should:  possess the basic knowledge in the area of information technology;  characterize themselves in this domain with necessary competitions on such a level that enables them the proper use of this technologies.In this article we are showing the results of a survey were carried out among teachers of pre - school education in both state and private nursery schools in the area of the city of Opole. The aim of the research was to define to what extent teachers of pre-school education use information technology in their work and in their private life.
Keywords: Informational Technology; kindergarten; teacher.